Retrospective Evaluation of a Large Nephrology Out-Patient Cohort - Ahmad, Waqar (Pakistan Journal of Kidney Diseases, 2025)
Background: chronic kidney disease remains a concern for both patients and health care providers due to its associated cost and complications. This study evaluates a large database of patients presenting to a nephrology out-patient clinic. Methods : retrospective review of about 4000 patients presenting to the outpatient nephrology clinic at a tertiary care hospital. Results: There were 4054 patients enrolled in the clinic, after cleaning of data for missing data or wrong entries 3217 subjects remained for evaluation. 1486 (46.19%) were diabetics and 1199 (37.27%) were hypertensive. Total of 1277 (%) patients had ESRD and 501 (%) were diabetics Conclusion: CKD is a growing burden of disease in Pakistan and our study highlights the underlying diabetes and hypertension as the leading causes of CKD.